Elderly care in the society 5.0 and kaigo rishoku in Japanese hyper-ageing society - Elsy, Putri (Jurnal Studi Komunikasi, 2020)
The Japanese demography is drastically changing. It has seen a rapid increase in the elderly population and a decrease in the birth rate. This caused Japan to be a hyper-ageing society. Japanese’s first Baby-boomers who were born in 1947-1949 are now entering old age. Elderly care is a major problem in Japan. Children and care-workers for elderly parents are scarce. Therefore, the second Baby-boomers (born in 1971-1974) aged 40-50 years old have quit working to care for their elderly parents. This situation is known as ‘kaigo rishoku.’ This study looked into the practice of elderly care in Japanese 5.0 Society. Society 5.0 is a concept developed by Japan. It is human-centred and technology-based. In society 5.0, robots and the internet play an essential role in human life. Therefore, we proposed a critical question: Can robots replace humans to care for the elderly in Society 5.0? This study used the qualitative method with a phenomenological approach and descriptive analysis. The results revealed that although robots can assist elderly care, due to the high cost, only a certain elderly can buy them. Therefore, in order for robots to become caregivers of the future, mass production is needed. Thus, robots can be marketed at relatively lower prices. However, sick elderly who live alone still need human assistance. On the one hand, technology helps human life in Society 5.0. On the other hand, the human touch is still necessary for elderly care.